Vernacular language in Firouz Shahnameh by Mohammad Bighami - زهرا سیدیزدی; فرزانه حکیمی پور (مطالعات زبانی و بلاغی)
FirouzShahnameh is the rest of the book that two of its volumes are called Darabnameh. This book was written by MohamadBighamy in ninth century, but it is clear that it has an older origin. After Samakayar and Darabname, Firouzshahnameh is one of the most important vernacular stories with great originality. Because of the prominent example of Persian simple proses that narrated and renarrated for people in this book, there are many vernaculars and colloquial expressions in this work. The wide application of colloquial elements in FirouzShahnameh had made it quite significant with regard to the criterion of colloquialism. The use of slang is one of the simplicity and popularity factors of this book. The present article interpret FirouzShahnameh and analyzes how it made use of the vernacular elements such as proverbs and colloquialism on different language levels starts from smallest language unit (i.e. phoneme) to the largest units (i.e. sentence). This study is carried out as a descriptive-analytical method. The results of this research showed that ironic expressions were the most frequent among other colloquial elements of FirouzShahnameh.